Complementary Organic Logic Gates on Plastic Formed by Self‐Aligned Transistors with Gravure and Inkjet Printed Dielectric and Semiconductors. (7th January 2016) - Higgins, Stuart G.; Muir, Beinn V. O.; Dell'Erba, Giorgio; Perinot, Andrea; Caironi, Mario; Campbell, Alasdair J.
Abstract : Complementary organic field‐effect transistors, inverters, NAND and NOR logic on plastic are demonstrated using a combination of nanoimprint lithography, self‐alignment, gravure, and inkjet printing. Sub‐micrometer channel lengths, electrode overlaps and sub‐100 nm dielectrics are compared to photolithographically patterned equivalents, as are inkjet and gravure printed semiconductors.